Identificación de bacterias benéficas mediante cultivos microbiológicos para el tratamiento de aguas residuales en el sector la calzada (humedal) del cantón Saquisilí, provincia de Cotopaxi, 2013 - Puruncajas Viera, Luis Javier (2013)
This study establishes the identification of beneficial bacteria which are in the “La Calzada” sector. Thus, a sample was done systematically, covering the entire area which took a representative number of samples in different parts of the wetland and at various depths. Basically, it determines the aerobic and the anaerobic conditions of an ecosystem under which microorganisms grow up. In this study a variety of methods were employed such as : The analytical, the scientific and the field one; Thus, the analytical method was used in the laboratory to identify the taxonomic in the bacteria and to determine the density and its applications, while the scientific method allowed justify whether the presumption raised is true....